1997
DOI: 10.1080/01652176.1997.9694758
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals and recent development in cryopreservation of bull and boar semen

Abstract: pes of lipid will aggregate in domains of gel-like (` frozen') lipid, thus excluding other lipid species that still remain in the liquid-crystalline (melted) state. Membrane proteins are also excluded from these gel domains and consequently find themselves in a non-physiological lipid environment (lateral phase separation (7,22). This is believed to impair the function of membrane proteins that are necessary for structural integrity (cytoskeleton) or ion metabolism (ion pumps). A second change in the environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 25 publications
1
45
0
7
Order By: Relevance
“…Similarly, Sukhato et al (2001) reported that automated freezing at the rate of À20 or À30°C/min yielded better sperm PM in buffalo compared to automated freezing at the rate of À10°C/min. It is, therefore, suggested that if the freezing rate is within the required values (50-100°C/min), this results in less excessive intracellular dehydration, less excessive intracellular solute concentrations, and less shrinkage of the cells (Mazur, 1984;Woelders, 1997). Moreover, at optimum freezing rates, the spermatozoa remain exposed to the unfavorable conditions for a shorter period of time (Woelders, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sukhato et al (2001) reported that automated freezing at the rate of À20 or À30°C/min yielded better sperm PM in buffalo compared to automated freezing at the rate of À10°C/min. It is, therefore, suggested that if the freezing rate is within the required values (50-100°C/min), this results in less excessive intracellular dehydration, less excessive intracellular solute concentrations, and less shrinkage of the cells (Mazur, 1984;Woelders, 1997). Moreover, at optimum freezing rates, the spermatozoa remain exposed to the unfavorable conditions for a shorter period of time (Woelders, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an L p value of 0.5 mm/min-atm and an activation energy of 3 kcal/mol results in a theoretically predicted optimal rate of freezing bovine sperm of ,5000 8C/min, when, in fact, experiments show that the 'optimal cooling rate' for bovine spermatozoa is 30 -100 8C/min, with a major decrease in viability after cooling at 300 8C/min (Rodriguez et al 1975, Robbins et al 1976, Foote & Parks 1993, Woelders 1997, Woelders & Malva 1998, Kumar et al 2003. One explanation of this discrepancy is that the values of water transport parameters at subzero temperatures in the presence of extracellular ice are markedly different than those reported in the literature at suprazero temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the worldwide cattle industry is based on artificial insemination and frozen semen, and cryopreservation has allowed exploitation of superior sires and achieved rapid, large-scale genetic improvement in cattle stocks coupled with a reduction in disease transmission (Foote 1999). This impact would not have been possible without successful freezing of bull spermatozoa (Parkinson & Whitfield 1987, Foote & Parks 1993, Woelders 1997, Vishwanath & Shannon 2000; also see Foote 2002 for a historical review on artificial insemination).…”
Section: Introductionmentioning
confidence: 99%
“…In response to this newly developed osmotic pressure gradient and the fact that water within the spermatozoon is slower to form ice crystals than the water in the surrounding medium, water passes out of the spermatozoa, particularly from the spermatozoon head, across the semi-permeable plasma membrane. Consequently, the spermatozoon becomes increasingly dehydrated (Andrabi, 2007;Watson, 2000;Woelders, 1997). The rate of efflux of water from the spermatozoa also depends upon the speed of temperature drop: the slower the drop, the greater would be the time needed for the efflux of water, and hence a much greater dehydration.…”
Section: Cryopreservation Of Semenmentioning
confidence: 99%
“…A successful cryopreservation should, therefore, aim at arriving at an optimum cooling rate that will provide a compromise between all these factors. There are two main temperature ranges of concern regarding damage to spermatozoa during freezing: the period of supercooling (0°C to -5°C) and the formation of ice crystals (-6°C to -15°C) (Woelders, 1997). Excessive supercooling results in a rapid ice formation, with the possibility of physical damage.…”
Section: Cryopreservation Of Semenmentioning
confidence: 99%